Influence of region and variety on fatty acid and tocopherol concentration of almond - Zhu Y.; Wilkinson K.; Wirthensohn M.G. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
This paper describes an investigation into the fatty acid and tocopherol concentration of several varieties of almonds grown in different almond-producing regions of Australia, as well as almonds grown in Spain and California. Considerable variation was observed not only in linoleic acid (15.7% – 29.9% of total lipids) and Vitamin E (8.2 mg – 21.5 mg/100 g) content, but also lipid (46.1 – 63.5 g/100 g), oleic acid (58.5% – 71.3% of total lipids), palmitic acid (5.9% – 7.5% of total lipids) and stearic acid (1.0% – 2.4% of total lipids) content. Understanding the influence of region and variety on almond composition will enable industry to make informed decisions with regards to almond breeding programs and the suitability of almond cultivars to particular growing regions.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)